2003
DOI: 10.2135/cropsci2003.1259
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nitrogen‐Use Efficiency in European Maize

Abstract: Maize (Zea mays L.) cultivars with improved N‐use efficiency would be beneficial for low‐input production systems. Our objective was to estimate quantitative genetic parameters to optimize breeding programs for improving productivity under low N levels. Results of 21 field experiments with European breeding materials belonging to the flint and dent gene pool are presented. The study was performed during 1989 and 1999 at several locations in typical maize growing regions of Germany and France. All experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(53 citation statements)
references
References 13 publications
8
42
0
3
Order By: Relevance
“…If LN stress in the target area is not serious (yield reduction is less than 10%, for example), selection for high yield in multiple environments can also increase yield performance under LN [26]. Nevertheless, with increasing LN stress, the correlation between yield under HN and LN decreases [27,28]. In the present study, when yield reduction was as high as 27.0%-56.1%, the correlation between the yields under HN and LN was no longer significant (Table 5).…”
Section: Genotype×nitrogen Interaction and The Pressure For Nue Selecmentioning
confidence: 99%
See 1 more Smart Citation
“…If LN stress in the target area is not serious (yield reduction is less than 10%, for example), selection for high yield in multiple environments can also increase yield performance under LN [26]. Nevertheless, with increasing LN stress, the correlation between yield under HN and LN decreases [27,28]. In the present study, when yield reduction was as high as 27.0%-56.1%, the correlation between the yields under HN and LN was no longer significant (Table 5).…”
Section: Genotype×nitrogen Interaction and The Pressure For Nue Selecmentioning
confidence: 99%
“…Selection in a LN environment can increase selection efficiency by 30%. If the correlation between yields under LN and HN is about 0.65, LN-tolerant genotypes selected in LN environments often achieve a higher yield under HN [28]. Therefore, breeding for NUE in maize should be conducted in both low and high N environment and the yield reduction under low N plots should be 25% to 60%.…”
Section: Genotype×nitrogen Interaction and The Pressure For Nue Selecmentioning
confidence: 99%
“…To determine yield response at sub--optimal or low levels of fertilization, specific low N screening locations need to be established which expose genetic variation in NUE under conditions reflective of the target environment (Inthapanya et al, 2000;Sahu et al, 1997;. Direct selection under low N screening has been found to be more efficient than indirect selection under high N (Presterl et al, 2003). 4.2.…”
Section: Crop Management Options For Increasing the Resilience Of Maimentioning
confidence: 99%
“…The authors showed that genotype × subregion interactions were low and selection in any subregion was likely to result in response in other subregions. The subdivision of a TPE into less heterogeneous subregions will only increase selection effi ciency if (i) genotype × subregion interactions are repeatable (Atlin et al, 2001), (ii) genotypic correlations among subregions are low (Presterl et al, 2003), and (iii) the increase in within-subregion genotypic variance achieved by subdivision can counterbalance loss in precision of genotypic means associated with division of testing resources because dividing a large TPE into smaller breeding targets is unlikely to result in more resources for testing within each new subregion (Atlin et al, 2000a(Atlin et al, , 2001Piepho and Möhring, 2005).…”
Section: Introductionmentioning
confidence: 99%